Impact of Climate Change on Health and Well-Being of People in Hindu Kush Himalayan Region: A Narrative Review - Dhimal, Meghnath; Bhandari, Dinesh; Dhimal, Mandira Lamichhane; Kafle, Naviya; Pyakurel, Prajjwal; Mahotra, Narayan; Akhtar, Saeed; Ismail, Tariq; Dhiman, Ramesh C.; Groneberg, David A.; Shrestha, Uttam Babu; Müller, Ruth (Frontiers in Physiology, 2021)
Climate change and variability affect virtually everyone and every region of the world but the effects are nowhere more prominent than in mountain regions and people living therein. The Hindu Kush Himalayan (HKH) region is a vast expanse encompassing 18% of the world’s mountainous area. Sprawling over 4.3 million km2, the HKH region occupies areas of eight countries namely Nepal, Bhutan, Afghanistan, Bangladesh, China, India, Myanmar, and Pakistan. The HKH region is warming at a rate higher than the global average and precipitation has also increased significantly over the last 6 decades along with increased frequency and intensity of some extreme events. Changes in temperature and precipitation have affected and will like to affect the climate-dependent sectors such as hydrology, agriculture, biodiversity, and human health. This paper aims to document how climate change has impacted and will impact, health and well-being of the people in the HKH region and offers adaptation and mitigation measures to reduce the impacts of climate change on health and well-being of the people. In the HKH region, climate change boosts infectious diseases, non-communicable diseases (NCDs), malnutrition, and injuries. Hence, climate change adaptation and mitigation measures are needed urgently to safeguard vulnerable populations residing in the HKH region.